2021
DOI: 10.1158/2159-8290.cd-20-1230
|View full text |Cite
|
Sign up to set email alerts
|

St. Jude Cloud: A Pediatric Cancer Genomic Data-Sharing Ecosystem

Abstract: Effective data sharing is key to accelerating research to improve diagnostic precision, treatment efficacy, and long-term survival in pediatric cancer and other childhood catastrophic diseases. We present St. Jude Cloud (https://www.stjude.cloud), a cloud-based data-sharing ecosystem for accessing, analyzing, and visualizing genomic data from >10,000 pediatric patients with cancer and long-term survivors, and >800 pediatric sickle cell patients. Harmonized genomic data totaling 1.25 petabytes are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
129
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 71 publications
1
129
0
Order By: Relevance
“…This result was robust across conditions of P3F knockdown or add-back, as well as when comparing FP-RMS versus FN-RMS cell lines ( Figure S3 F). On subsequent analyses of RNA sequencing (RNA-seq) profiles from a cohort of PAX3-FOXO1 + FP-RMS versus FN-RMS (embryonal, ERMS, subtype) patients ( Downing et al., 2012 ; McLeod et al., 2021 ), we once again found that relatively few genes associated with PAX3-FOXO1 binding were differentially expressed in patients based on PAX3-FOXO1 fusion status ( Figure S3 G). Across P3F-binding site categories, less than 30% of proximal genes were differentially expressed in patient samples (average 23.7%, fold change >2, adjusted p value < 0.05), and these genes showed similar likelihood of being up- or down-regulated in P3F+ patients.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…This result was robust across conditions of P3F knockdown or add-back, as well as when comparing FP-RMS versus FN-RMS cell lines ( Figure S3 F). On subsequent analyses of RNA sequencing (RNA-seq) profiles from a cohort of PAX3-FOXO1 + FP-RMS versus FN-RMS (embryonal, ERMS, subtype) patients ( Downing et al., 2012 ; McLeod et al., 2021 ), we once again found that relatively few genes associated with PAX3-FOXO1 binding were differentially expressed in patients based on PAX3-FOXO1 fusion status ( Figure S3 G). Across P3F-binding site categories, less than 30% of proximal genes were differentially expressed in patient samples (average 23.7%, fold change >2, adjusted p value < 0.05), and these genes showed similar likelihood of being up- or down-regulated in P3F+ patients.…”
Section: Resultsmentioning
confidence: 87%
“…PAX3-FOXO1 signals and peaks are directly comparable across cell lines and conditions, as they have been collectively normalized for this study. Clinical RNA-seq data for pediatric rhabdomyosarcoma patients used for analysis in this study were obtained from the St. Jude Cloud ( McLeod et al., 2021 ). This paper does not report original code.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was robust across conditions of P3F knockdown or add-back, as well as when comparing FP-RMS versus FN-RMS cell lines (Figure S3F). Subsequent analyses of RNA-seq profiles from a cohort of PAX3-FOXO1+ FP-RMS vs. FN-RMS (embryonal, ERMS, subtype) patients (Downing et al, 2012;McLeod et al, 2021), we once again found that relatively few genes associated with PAX3-FOXO1 binding were differentially expressed in patients based on PAX3-FOXO1 fusion status (Figure S3G). Across P3F binding site categories, less than 30% of proximal genes were differentially expressed in patient samples (average 23.7%, fold change > 2, adjusted p-value < 0.05), and these genes showed similar likelihood of being up-or down-regulated in P3F+ patients.…”
Section: Cellular and Genomic Localization Of The Pax3-foxo1 Fusion Transcription Factor To Inactive Chromatinmentioning
confidence: 79%
“…PAX3-FOXO1 signals and peaks are directly comparable across cell lines and conditions, as they have been collectively normalized for this study. Clinical RNA-seq data for pediatric rhabdomyosarcoma patients used for analysis in this study were obtained from the St. Jude Cloud (McLeod et al, 2021). Only publicly available algorithms were used in the analysis of datasets presented in this study.…”
Section: Methodsmentioning
confidence: 99%